2022
DOI: 10.3389/fneur.2022.930303
|View full text |Cite
|
Sign up to set email alerts
|

Reduced wrist flexor H-reflex excitability is linked with increased wrist proprioceptive error in adults with cerebral palsy

Abstract: Although most neurophysiological studies of persons with cerebral palsy (CP) have been focused on supraspinal networks, recent evidence points toward the spinal cord as a central contributor to their motor impairments. However, it is unclear if alterations in the spinal pathways are also linked to deficits in the sensory processing observed clinically. This investigation aimed to begin to address this knowledge gap by evaluating the flexor carpi radialis (FCR) H-reflex in adults with CP and neurotypical (NT) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…These clinical findings have been corroborated by studies showing alterations in neural networks processing proprioception, such as the inferior parietal lobe, in children with ASD [69]. The present findings confirmed poorer proprioception acuity and proprioceptive reactive behaviors in children with CP, which can be explained by the influence of spasticity on muscle lengthening (which are characteristic of the CP condition), as well as the abnormalities in neural tracts and afferent cortical perception [35,64]. Surprisingly, our results do not show abnormal proprioception in children with ASD, when compared to TDPs.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These clinical findings have been corroborated by studies showing alterations in neural networks processing proprioception, such as the inferior parietal lobe, in children with ASD [69]. The present findings confirmed poorer proprioception acuity and proprioceptive reactive behaviors in children with CP, which can be explained by the influence of spasticity on muscle lengthening (which are characteristic of the CP condition), as well as the abnormalities in neural tracts and afferent cortical perception [35,64]. Surprisingly, our results do not show abnormal proprioception in children with ASD, when compared to TDPs.…”
Section: Discussionsupporting
confidence: 88%
“…Extensive research has reported proprioceptive impairments in children with CP [ 21 , 22 , 23 , 64 , 65 ], impacting activity, participation and functional performance [ 22 , 23 ]. Proprioceptive deficits in children with CP have been associated with motor function impairment and spasticity [ 25 , 64 , 66 ] and have been attributed to abnormalities of spino- and thalamo-cortical neural tracts, abnormal cortical activity and lower muscle H-reflex excitability [ 35 , 66 , 67 ]. On the other hand, previous research in children with ASD has reported diminished proprioceptive performance, in the form of poor perception of joint position and altered speed-based proprioception [ 19 , 63 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, these combined results suggest that the altered PMBR seen for the persons with CP might indicate greater uncertainty about the sensory feedback after the completion of the motor task 23 , 24 . We speculate that this uncertainty is likely related to the altered sensory processing noted across the behavioral 1 , 69 72 and neurophysiology literature for persons with CP 13 , 62 , 73 – 78 . As such, the altered sensory processing at both the cortical and spinal cord level likely has cascading effects on the sensorimotor system and affects the fidelity assessment of adjusted motor outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Lastly, the participants completed the wrist position test, which quantifies the ability of the participant to correctly identify the joint’s position following a movement performed by the examiner 61 , 62 . The test consists of 20 predetermined wrist flexion and extension angles, where the examiner passively moved the wrist to the endpoint angular position as the participant’s vision of the wrist position was occluded.…”
Section: Methodsmentioning
confidence: 99%